Genetic diversity, biofilm and virulence characteristics of Listeria monocytogenes in salmon sushi. (February 2021) - Ramires, Tassiana; Kleinubing, Natalie Rauber; Iglesias, Mariana Almeida; Vitola, Helena Reissig Soares; Núncio, Adriana Souto Pereira; Kroning, Isabela Schneid; Moreira, Gustavo Marçal Schmidt Garcia; Fiorentini, Ângela Maria; da Silva, Wladimir Padilha
Graphical abstract: Highlights: Listeria monocytogenes contamination in salmon sushi was detected in six samples (21.4%). All the isolates belonged to serotype 4b. The main virulence genes were observed in all isolates, except the inlB in two isolates. The persistence of some clones was verified for at least one month in two establishments. All isolates showed ability to form biofilm in stainless steel. Abstract: Sushi is a ready-to-eat (RTE) food prepared from raw or cooked fish that is widely consumed worldwide. Listeria monocytogenes is the foodborne pathogen most commonly associated with RTE and fish products. The aim of the present study was to evaluate the presence of L. monocytogenes in salmon sushi commercialized in Pelotas city, Brazil, and to evaluate the genetic diversity, biofilm-forming ability in stainless steel, and virulence characteristics of the isolates. Four sampling events were carried out in seven specialized sushi establishments totaling 28 sushi pools. Listeria monocytogenes was detected in six samples (21.4%) from two establishments (28.6%). All isolates belonged to serotype 4b and carried the prfA, plcA, plcB, hlyA, mpl, actA, inlA, inlC, inlJ, and iap genes. The inlB gene was not detected in two isolates. The PFGE analysis grouped the isolates into four pulsotypes. All isolates had the ability to form biofilm on stainless steel and the average of biofilm formation counts varied between 6.4 and 7.2 log CFU.cm −2 . The isolates harbored the biofilm-related genes agrA, agrB, agrC, agrD, and prfA, with the exception of two isolates that did not harbor the agrD gene. The presence of L. monocytogenes in RTE sushi is a concern, demonstrating that sushi consumption may be a risk of human listeriosis. Furthermore, it was possible to identify the persistence of this pathogen for at least one month (pulsotypes III and IV), in two establishments (A and G), highlighting the need for improving the cleaning and sanitation procedures in establishments that commercialize RTE sushi.